ISO 14000 environmental management standards : engineering and financial aspects - Morris, Alan S., 1948- (Wiley, 2004)
This book covers the cross-disciplinary areas between management issues and engineering issues relevant to implementation of Environmental Management Systems (EMS) to the ISO 14000 series standards. It summarises the requirements set by ISO14001 and considers the management and engineering policies needed to satisfy these requirements and achieve ISO 14001 certification. Unique approach by integrating environmental management and engineering considerationsAvoids overuse of complicated technical jargonDetailed coverage of measurement and calibration standards℗¡to meet ISO14001Provides example of.